LOS TOMBOLOS CATEDRAL Y UVITA - Saénz G., Rodrígo; Magallón Molina, Florencio; Cevo Guzman, Juan; Flores Silva, Eusebio (Revista Geográfica de América Central., 2011)
No presenta resumen este articulo.